In Silico Study of Anti-Inflammatory Potential of 1.8-Cineole against Cox-2 and TLR-2 - Sianiwati Goenharto (Journal of Global Pharma Technology, 2020)
Objective: To determine the anti-inflammatory activity of 1.8-cineole against COX-2 and TLR-2 using an in silico approach. Methods: In silico studies were conducted using the Molegro Virtual Docker (MolDoc) program to predict the anti-inflammatory potency of 1.8-cineole against COX-2 and TLR-2 receptors. Results: MolDoc score showed that 1,8-cineole (-49.1236) could be predicted to be an anti-inflammatory ligand demonstrating lower activity than diclofenac or COX-2 (-106.8010) ligand. 1,8-cineole (-42.7930) can also be predicted to be an anti-inflammatory ligand with lower activity than TLR-2 / CAS_673 ligand (-56.5640). Conclusion: 1.8-cineole possesses anti-inflammatory potential against COX-2 and TLR-2 receptors based on an in silico predictive study.